Edukasi Kesehatan Reproduksi (Personal Hygiene, Pubertas, Perubahan Fisik) Di Boarding School Man 2 Surakarta - Nevia Zulfatunnisa; Juda Julia Kristiarini; Eka Vicky Yulivantina (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Reproductive health is very important for everyone to understand, especially young women. According to WHO, adolescents are defined as residents in the age range 10-19 years, according to the Republic of Indonesia Minister of Health Regulation Number 25 of 2014, adolescents are residents in the age range 10-18 years and according to the Population and Family Planning Agency (BKKBN) the age range for adolescents is 10-18 years. 24 years old and not married. Adolescence is a period of transition from childhood to adulthood which is marked by physical, emotional and psychological changes. During this period, there was rapid growth and development, both physical and mental. This adolescent phase is also the time for the maturation of human reproductive organs, so it is often called the transition period. In this age range, teenagers are generally pursuing their formal education at junior high school, high school and college. Currently, access to information for Indonesian teenagers regarding reproductive health is still very limited because many people still think that sexuality is a taboo subject to discuss. Limited access to information regarding reproductive health results in a lack of knowledge, characteristics and risk behavior in adolescents which has an impact on the reproductive health status of adolescents. This situation requires the availability of caring health services for adolescents that can meet the health needs of adolescents, especially services for reproductive health that are friendly to adolescents To provide reproductive health education (personal hygiene, puberty, physical changes to female students at the MAN 2 Surakarta Boarding School. This community service is carried out based on the current phenomenon, especially what happened to the female students of Boarding School MAN 2 Surakarta, namely that there is still a lack of information obtained about reproductive health. This community service will be implemented on August 26 2023, starting with preparing a proposal, preparing educational media in the form of PPTs, leaflets, preparing the audience and place. This reproductive health education was attended by 50 female students. This reproductive health education was carried out in the hall of the MAN 2 Surakarta Boarding School. The results of community service show that there is an increase in female students' knowledge about reproductive health, especially regarding personal hygiene, puberty and physical changes.